Motor performance as a predictor of blood levels of ammonia and inflammatory biomarkers in patients with liver cirrhosis - Constanza San Martín Valenzuela; Juan José Gallego; Amparo Urios; Patricia Correa-Ghisays; Rafael Tabarés-Seisdedos; Carmina Montoliu (PLoS ONE, 2025)
Liver cirrhosis can present with complications such as hyperammonemia and inflammation, and the consequent appearance of minimal hepatic encephalopathy (MHE), which has been associated with poorer motor performance. Our aim was to analyze whether motor impairment would predict blood levels of ammonia and inflammatory factors in cirrhotic patients, independently of cognitive impairment. Blood was extracted from 67 cirrhotic patients from two hospitals in Valencia (Spain) (41.79% with MHE, diagnosis by Psychometric Hepatic Encephalopathy Score). Blood ammonia and plasma levels of interleukins (IL-6, IL-13, IL-18, IL-21, IL-22, IL-23, TNF-α, TGF-β) and chemokines (CCL20, CX3CL1, CXCL13, CCL2) were measured by micro-diffusion and ELISA, respectively. Gait, balance, hand strength, and manual motor speed were evaluated with biomechanical tools. All measurements were performed at University of Valencia, Spain. Motor outcomes were used as predictors in multiple linear regression analysis to determine their predictive capacity on blood ammonia and inflammatory factors. We found that levels of blood ammonia and TNF-α were significantly predicted by the set of motor parameters with a coefficient of determination (R2)>0.50, particularly by balance performance through the movement and velocity of Center of Pressure across the balance test. On the other hand, the models for IL-13, IL-21, CX3CL1, IL-6, CCL2, yielded an R2 varying between 0.31–0.39. Lastly, R2 was between 0.29 and 0.16 for the cytokines CXCL13, IL-22, CCL20, IL-18, and TGF-β. Beside balance outcomes, gait speed and swing phase, as well as grip and lateral pinch strength, and hand motor speed, were frequent predictors in the models calculated. In conclusion, motor performance can predict blood levels of ammonia and cytokines in patients with liver cirrhosis, independently of the cognitive impairment present. Motor impairment could serve as an early, non-invasive indicator of disease severity, indicating the utility of conducting these tests in daily clinical practice and in follow-up studies.